ANALISIS ADOPSI INOVASI PROGRAM SEKOLAH LAPANG PENGELOLAAN TANAMAN TEPADU (SL-PTT) UNTUK PENINGKATAN PRODUKTIVITAS PADI - Saeroji, Saeroji (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2018)
The program of Farmers Field School on Integrated Crop Management (FFS - ICM) represent an is farmers non-formal education place by synergies and vision of environment so that its become cultivation efficiently, high productivity and sustainable. The efficacy indicator of the success of the FFS - ICM Program that is improvement of the knowledge, skill, attitude change, applying of good agriculture practices, improvement of productivity and sustainability and also its replication. One of the districts of rice production centre in East Java which have executed FFS - ICM Program that is Pasuruan District, but there are many members of group farmers which not yet executed the program. Innovation Adoption research on FFS - ICM Program to increase rice productivity aims to describe of execution of FFS - ICM Program, explains the farmers adoption level, analyse the rice productivity level and analyse the relationship between the adoption level of FFS - ICM Program with the level of rice productivity. Method analysis of date is used t-test and rank spearman correlation. Result of analysis indicate that technological adoption level of farmer in the research area which including high category equal to 86.75%. The average productivity of rice has increased by 1.92 tons/hectare. Result of relation analysis between adoption of FFS-ICM Program with rice productivity, at trust level 95%, showing there are significant correlation between level adoption of FFS-ICM Program with rice productivity.